2021
DOI: 10.1002/smtd.202100632
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Tissue‐Specific, Multiscale Microvasculature with a Capillary Network for Prevascularized Tissue

Abstract: Although there are various pre‐existing technologies for engineering vasculatures, multiscale modeling of the architecture of human vasculature at a capillary scale remains a challenge. In this study, a novel technology is developed for the production of a functional, multiscale microvasculature comprising of endothelialized channels and tissue‐specific capillary networks. Perfusable, endothelialized channels are bioprinted, after which angiogenic sprouts are grown into user‐designed capillary networks. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…Such motifs are present in natural hydrogel materials such as collagen, gelatin, gelatin methacrylol, fibrin, and hyaluronic acid [ 55 , 58 , 61 ]. In alginate, agarose, and PEG hydrogels, such motifs are missing but can be added to the bioink formulation [ 42 , 62 , 63 ]. In a systematic investigation of the viability of human umbilical vein endothelial cells (HUVECs) in various hydrogels of standardized concentrations, Benning et al demonstrated that fibrin, collagen 1, Matrigel, and gelatin hydrogels maintain the viability of integrated HUVECs and enable the attachment of cells [ 64 ].…”
Section: Strategies Before 3d Bioprinting: Materials Properties and B...mentioning
confidence: 99%
See 4 more Smart Citations
“…Such motifs are present in natural hydrogel materials such as collagen, gelatin, gelatin methacrylol, fibrin, and hyaluronic acid [ 55 , 58 , 61 ]. In alginate, agarose, and PEG hydrogels, such motifs are missing but can be added to the bioink formulation [ 42 , 62 , 63 ]. In a systematic investigation of the viability of human umbilical vein endothelial cells (HUVECs) in various hydrogels of standardized concentrations, Benning et al demonstrated that fibrin, collagen 1, Matrigel, and gelatin hydrogels maintain the viability of integrated HUVECs and enable the attachment of cells [ 64 ].…”
Section: Strategies Before 3d Bioprinting: Materials Properties and B...mentioning
confidence: 99%
“…Moreover, several bioinks consisting of different supporting materials specifically adapted to the respective cell compositions can be applied in combination on a bioprinting platform [ 14 , 46 ]. HUVECs have been extensively studied for application in biofabrication [ 14 , 21 , 27 , 33 , 39 , 46 , 47 , 50 , 59 , 63 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. Functional vessel endothelium produces nitric oxide, thrombomodulin, and tissue plasminogen activator, all inhibitors of thrombus formation [ 36 , 40 ].…”
Section: Strategies Before 3d Bioprinting: Materials Properties and B...mentioning
confidence: 99%
See 3 more Smart Citations